KAJIAN UNSUR INTRINSIK DALAM NOVEL DEAR ALLAH KARYA DIANA FEBI (SUATU TINJAUAN STRUKTURAL SEMIOTIK) - Nahrin Indriani; Ika Martanti Mulyawati (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Abstract This study aims to explain: (1) the intrinsic elements of the novel Dear Allah by Diana Febi, (2) the relationship between setting, plot, and characterizations tied to the theme in the novel Dear Allah, and (3) the form of the relationship between signs and references in the form of indexes, symbols, as well as icons in the novel Dear Allah. This research uses the content method with a qualitative description approach. The validity of the data is obtained through observation, perseverance and thoroughness of the reader in reading and understanding the contents of the novel, as well as the triangulation method. The results of the study explain that the novel Dear Allah has a forward plot with three stages, namely the first stage is an introduction, then the middle stage is the emergence of a conflict or problem, and the last stage is a resolution. The novel Dear Allah by Diana Febi ends with happiness for the main characters, namely Naira and Wildan. They both can finally live together happily and they are grateful to have been blessed with a child. The story of this novel is set in a mosque, room, Wildan's house, hospital, living room, operating room, and hall of the nursing center. All intrinsic elements are interrelated and tied to the theme. The form of the relationship between signs and references can be found in the novel Dear Allah in the form of icons, which consist of diagrammatic icons, topological icons, and metaphorical icons. Then, there are also indexes and symbols. Keywords: Novel, Intrinsic, Structural Semiotic.